Assessment of anti-diabetic potential of Lentinula edodes using diabetes screening tools, including glycemic index and glycemic load - Makkar, Sujata; Nehra, Kiran; Singh, Ajay (Mushroom Research, 2022)
Changes in dietary practices like overconsumption of energy-dense foods and a lower intake of fruits and vegetables have been recognized as primary contributors to the globally rising incidence of lifestyle-related diseases such as diabetes and cardiovascular disease. The usage of plant-based foods has been shown to reduce the risk of such chronic diseases. In this direction, the current study's objective was to conduct an in-vivo evaluation of the anti-diabetic potential of five different strains of the medicinal mushroom Lentinula edodes in healthy adult Sprague Dawley rats by using screening tools such as the glycemic index (GI) and Glycemic load (GL). For this, 36 rats were distributed into six groups, fasted overnight, and then given oral administration of glucose as a reference to one group, and each of the five different strains of the test mushroom to the rest of the five groups. Blood samples were drawn from the tail vein before (zero minutes) and after administration of either glucose or the different strains of the mushroom at 15, 30, 45, 60, 90, and 120-minute intervals. The results showed that the lowest GI values were found at 13.2% in strain DMRO-356, followed by that in strain DMRO-388 (13.3%), DMRO-34 (14.8%),  DMRO-35 (15.9%), and DMRO-623 (17.2%); all values falling under the low GI category. Furthermore, the glycemic load (GL) of the mushroom strains revealed that DMRO-356 had the lowest GL value (7.53%), followed by DMRO-388 (8.82%), DMRO-35 (8.92%), DMRO-623 (10.24%), and DMRO-34 (10.24%). (10.25%). Among the five tested mushroom strains, both the GI value (13.2%) and the GL value (7.53%) were found to be the lowest in the strain DMRO-356. Since lower GI  and GL values have a better response for glucose absorption in the blood sample, the present study results indicate that these different strains of L. edodes may be beneficial for diabetic patients and thus may also help prevent human diseases such as cardiac problems.